2020
DOI: 10.1101/2020.04.13.039818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insight into biogeochemical models from Scale Transition Theory: A dimensionless, scale-free approach

Abstract: Leading an effective response to the accelerating crisis of anthropogenic climate change will require improved understanding of global carbon cycling. A critical source of uncertainty in Earth Systems Models (ESMs) is the role of microbes in mediating both the formation and decomposition of soil organic matter, and hence in determining patterns of CO2 efflux. Traditionally, ESMs model carbon turnover as a first order process impacted primarily by abiotic factors, whereas contemporary biogeochemical models ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Significant challenges remain because while microbial communities are diverse both functionally and taxonomically, successful modelling requires simplification and it is not yet clear which axes of microbial community variation demand focus. Furthermore, upscaled estimates from even the simplest mechanistic models are certain to violate mean‐field assumptions if they do not account for fine‐scale variability (Wilson & Gerber, 2020), which is of particular concern in microbial communities because ecologically impactful interactions occur at microscopic scales (e.g. Boddy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Significant challenges remain because while microbial communities are diverse both functionally and taxonomically, successful modelling requires simplification and it is not yet clear which axes of microbial community variation demand focus. Furthermore, upscaled estimates from even the simplest mechanistic models are certain to violate mean‐field assumptions if they do not account for fine‐scale variability (Wilson & Gerber, 2020), which is of particular concern in microbial communities because ecologically impactful interactions occur at microscopic scales (e.g. Boddy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Starting with a model at a finer scale—(a) ecosystem, (b) community or (c) physiological—we attempt to predict the system's behaviour at a broader scale by naively reapplying lower‐level traits. In each case, such extrapolation fails due to emergent processes (Bradford et al., 2017; Wilson & Gerber, 2020) that must be explicitly included in order to make accurate predictions.…”
Section: The Unresolved Problem Of Scale In Trait‐based Modelsmentioning
confidence: 99%
“…A related approach (Barbier et al., 2018) uses techniques from statistical physics to predict community properties from average interactions within a community; here, traits are not fixed parameters but rather statistical distributions. Indeed, application of such techniques to global microbial biogeochemistry has demonstrated that they might be used in Earth system contexts to capture local‐scale heterogeneity (Wilson & Gerber, 2020).…”
Section: Unifying the Scales Of Microbial Biogeochemistrymentioning
confidence: 99%
See 1 more Smart Citation